An Efficient Water Marking and Intrusion Detection System Framework for Insider Attack Detection in Cloud Based E-Healthcare Data Management - Palani , S.; Rameshbabu, K. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The health care industries in recent years have been facing numerous challenges towards the implementation of electronic health records in preserving the privacy of patients and keeping intact their information. The impact of e-Healthcare system has resulted in inappropriate investigation of patient’s health records. This in turn has affected the cost effectiveness and data consumption. Therefore, the liability towards these two factors is greatly affected. Hence, lack of an appropriate system for detection brings about data breaches. The concept of enabling eHealth systems on the cloud environment will provide a practical solution to the existing problem failing which health records are prone to attacks and intrusion. Any such attacks consequently incur misrepresentation of data which may prove to be endangering for the patients. While the recent researches have failed to throw light on identifying a malignant insider, the current research proposes a novel method which is inbuilt of options for identifying a destructive insider.The effective resource allocation module and watermarking methods used in conjunction with Intrusion Detection System (IDS) for Cloud-based Healthcare System are the main topics of this article. Regarding data storage and malware attack detection, the suggested solution is thought to be more effective and functional. This work uses the Improved Cuckoo Search Algorithm (ICSA) and Convolutional Neural Network for task scheduling and resource allocation (CNN). The spatial domain is reliant on the watermark’s hindrance on the pictures’ least significant bits (LSB) when a later watermarking approach is utilised. Finally, an intrusion assault detection framework is used for identification in order to determine the attackers of information notification in the e-Health care system. In order to defend against data modification attacks and to identify intruders, watermarking is crucial. Thus, this investigational assessment shows the proposed research which delivers efficient storage of health data in a highly secured environment.